2009
DOI: 10.1111/j.1540-4560.2009.01626.x
|View full text |Cite
|
Sign up to set email alerts
|

Context Matters: Explaining How and Why Mobilizing Context Influences Motivational Dynamics

Abstract: The emphasis in the social-psychological collective action literature is on why individuals take part in collective action; however, it does not elaborate on how different mobilizing contexts may appeal to distinct motivational dynamics to participate. The present study connects the microlevel of motivational dynamics of individual protesters with the mesolevel of social movement characteristics. To do so a field study was conducted. Protesters were surveyed in the act of protesting in two different demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
124
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 138 publications
(133 citation statements)
references
References 26 publications
5
124
0
4
Order By: Relevance
“…Although the basic content and mechanisms of these motives are consistent across many situations, specific differences can be discovered depending on unique contexts (Van Stekelenburg and Klandermans, 2014;Van Stekelenburg et al, 2009). Generally speaking, most on-and offline collective action in the contemporary Chinese context does not oppose the existing political system and ideology because of Confucianism and market economic values.…”
Section: Motivations For Par Ticipation In Online Collective Actionmentioning
confidence: 99%
“…Although the basic content and mechanisms of these motives are consistent across many situations, specific differences can be discovered depending on unique contexts (Van Stekelenburg and Klandermans, 2014;Van Stekelenburg et al, 2009). Generally speaking, most on-and offline collective action in the contemporary Chinese context does not oppose the existing political system and ideology because of Confucianism and market economic values.…”
Section: Motivations For Par Ticipation In Online Collective Actionmentioning
confidence: 99%
“…Recently however, van Zomeren et al, (2010) showed that efficacy and group identification are mutually enhancing and recursive. There have also been analyses of effects of emotion (Stürmer, & Simon, 2009), and violated sacred values and ideology (Giguère & Altran, 2009;van Stekelenburg et al, 2009). However the absence of the analysis of the effects of consensually shared beliefs about the causes of phenomena in shaping action (Kluegel & Smith, 1986) renders the account of motivators and constrains incomplete.…”
Section: Conclusion: Summative Conceptual Alignmentmentioning
confidence: 99%
“…Stürmer & Sturmer (2009) recently motivated for an addition pathway, 'emotion'. Other Scholars have argued for supplementary pathways including willingness to express one's view or ideology, the protection of sacred values (Ginges & Altran, 2009;van Stekelenburg et al, 2009) and individual enhancement motive (Tropp & Brown, 2004). Bluic et al (2007: 19) showed that while group identification and efficacy influence collective action, the statistical variance contributed to action by these variables have been weak, indicating that there are other mediating factors meriting attention beside these instrumental concerns.…”
Section: Relative Deprivation and Social Identity Inspired Explanationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rather than replacing instrumentality as an explanatory paradigm, identification added to the explanation as a second pathway. Van Zomeren and colleagues (2004) Klandermans, & van Dijk 2009). In order to develop the shared grievances and shared emotions a shared identity is needed (see figure).…”
Section: Contemporary Social Psychological Approachesmentioning
confidence: 99%